Biopower over the Practice of Body Commercialization for Women Commercial Sex Workers through Digital Application - Febriana Aulia; Yeby Ma'asan Mayrudin (Indonesian Democracy Research Center, 2026)
This article discusses how digital transformation has driven a shift in prostitution promotion practices from traditional to digital. This article focuses on the digital application called MiChat, a chat application frequently used by sellers and buyers. This study aims to analyze online prostitution practices and understand how women commercial sex workers (CSWs) who use the MiChat application interpret and negotiate power over their bodies amidst economic pressures, social stigma, and weak legal protection. This study uses qualitative methods with a phenomenological approach to explore the lived experiences of female CSWs as research subjects. Data were collected through in-depth interviews with female CSWs who use MiChat, non-participant observation, and documentation. The results indicate that online prostitution is interpreted as a survival strategy and a space for relative bodily autonomy. Female CSWs have control over their working hours, client selection, and setting service boundaries through digital media. However, this power over their bodies is unstable due to limitations imposed by social stigma, the risk of violence, and unclear legal status.